Non-Thyroidal Illness Syndrome in Patients Exposed to Indoor Air Dampness Microbiota Treated Successfully with Triiodothyronine - Somppi, Taija Liisa (Frontiers in Immunology, 2017)
Abstract Long-term exposure to dampness microbiota induces multi-organ morbidity. One of the symptoms related to this disorder is non-thyroidal illness syndrome (NTIS). A retrospective study was carried out in nine patients with a history of mold exposure, experiencing chronic fatigue, cognitive disorder and different kinds of hypothyroid symptoms despite provision of levothyroxine (3,5,3',5'-tetraiodothyronine, LT4) monotherapy. Exposure to volatile organic compounds (VOC) present in water-damaged buildings including metabolic products of toxigenic fungi and mold-derived inflammatory agents can lead to a deficiency or imbalance of many hormones, such as active T3-hormone. Since the 1970s, the synthetic prohormone, levothyroxine (LT4), has been the most commonly prescribed thyroid hormone in replacement monotherapy. It has been presumed that the peripheral conversion of T4 (3,5,3',5'-tetraiodothyronine) into T3 (3,5,3'-triiodothyronine) is sufficient to satisfy the overall tissue requirements. However, evidence is presented that this not the case for all patients, especially those exposed to indoor air molds. This retrospective study describes the successful treatment of nine patient in whom NTIS was treated with T3-based thyroid hormone. The treatment was based on careful interview, clinical monitoring and laboratory analysis of serum free T3 (FT3), reverse T3 (rT3) and thyroid stimulating hormone (TSH), free T4 (FT4), cortisol and dehydroepiandrosterone (DHEA) values. The ratio of FT3/rT3 was calculated. In addition, some patients received adrenal support with hydrocortisone and DHEA. All patients received nutritional supplementation and dietary instructions. During the therapy, all nine patients reported improvements in all of the symptom groups. Those who had residual symptoms during T3-based therapy, remained exposed to indoor air molds in their work places. Four patients were unable to work and had been on disability leave for a long time during LT4 monotherapy. However, during the T3-based and supportive therapy, all patients returned to work in so-called “healthy” buildings. The importance of avoiding mycotoxin exposure via the diet is underlined as DIO2 genetic polymorphism and dysfunction of DIO2 play an important role in the development of symptoms that can be treated successfully with T3 therapy.